Some Unfinished Business in the Professionalization of the Personnel Man / Le spécialiste du personnel, un professionnel ? - Hall, Oswald (Relations industrielles / Industrial Relations, 1961)
SummaryPersonnel men tend to define themselves as professionals. To find out whether they are justified in so doing, the Author describes the earmarks of a profession: specialization, spécific and unstandardized nature of the service to the client (who is more than just a customer), episodic and direct relationship between professional and client. With such criteria in hand, the Author argues that it is improbable that personnel work can be practised along the lines of a professional model; the bureaucratic model here appears more relevant.